2014
DOI: 10.1037/a0032789
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sexual aggression in male college students in Brazil.

Abstract: The study is the first to provide data on risk factors for sexual aggression in male college students in Brazil. A total oí N = 286 participants took part in the study, of whom a subsample of n = 120 participated in two measurements separated by a 6-month interval. Cognitive (i.e., risky sexual scripts, normative beliefs), behavioral (i.e., pornography use, sexual behavior patterns), and biographical (i.e., childhood abuse) risk factors were linked to sexual aggression both cross-sectionally and longitudinally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 56 publications
7
47
0
Order By: Relevance
“…To address those gaps and better orient public policies, I outline some suggestions for future research in Brazil: (1) self-report studies on sexual aggression and victimization with representative samples of the Brazilian population, identifying the differences across the five major geographic regions; (2) studies that address sexual aggression from a developmental and longitudinal perspective, from young age until late adulthood, seeking to understand the onset, severity, and persistence of the problem over the years; few Brazilian studies have addressed sexual victimization and perpetration prospectively 49,51 ; (3) studies that differentiate between childhood sexual abuse and sexual aggression i.e., sexual victimization before and after age 14, respectively; (4) studies that address sexual aggression and victimization in both men and women, taking sexual orientation and skin color into consideration; (5) studies that address incidence of sexual aggression in the previous year, using a behaviorally specific description of the legal definition of rape in Brazil, such as proposed by SES 16 , so that rates can be directly compared to the official data on rape in Brazil; (6) studies that confirm if, and explain why, specific social groups (e.g., homosexuals and bisexuals, and university students) may have higher vulnerability for sexual victimization and perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…To address those gaps and better orient public policies, I outline some suggestions for future research in Brazil: (1) self-report studies on sexual aggression and victimization with representative samples of the Brazilian population, identifying the differences across the five major geographic regions; (2) studies that address sexual aggression from a developmental and longitudinal perspective, from young age until late adulthood, seeking to understand the onset, severity, and persistence of the problem over the years; few Brazilian studies have addressed sexual victimization and perpetration prospectively 49,51 ; (3) studies that differentiate between childhood sexual abuse and sexual aggression i.e., sexual victimization before and after age 14, respectively; (4) studies that address sexual aggression and victimization in both men and women, taking sexual orientation and skin color into consideration; (5) studies that address incidence of sexual aggression in the previous year, using a behaviorally specific description of the legal definition of rape in Brazil, such as proposed by SES 16 , so that rates can be directly compared to the official data on rape in Brazil; (6) studies that confirm if, and explain why, specific social groups (e.g., homosexuals and bisexuals, and university students) may have higher vulnerability for sexual victimization and perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…In international research (African and Indian samples), having a greater number of sexual partners is a significant risk factor for intimate and nonintimate partner rape (D’Abreu & Krahé, 2014; Dunkle et al, 2006; Go et al, 2010; Jewkes et al, 2006; Jewkes, Nduna, Jama Shai, & Dunkle, 2012; Kalichman et al, 2007; Kalichman et al, 2005; Simbayi et al, 2006; Townsend et al, 2011; Tsai et al, 2011). For example, a history of SV is associated with an increased likelihood of having five or more partners in the past three months (Townsend et al, 2011).…”
Section: Sexual Partners and Sv Perpetrationmentioning
confidence: 99%
“…For example, a history of SV is associated with an increased likelihood of having five or more partners in the past three months (Townsend et al, 2011). In both domestic and international research (samples from Brazil and South Africa), men’s number of sexual partners is related to their SV perpetration prospectively and longitudinally in a variety of samples (Abbey & McAuslan, 2004; Abbey et al, 2012; D’Abreu & Krahé, 2014; Jewkes et al, 2012; Thompson, Swartout, & Koss, 2013). Despite the hetereogeneity in samples and measures, each of these studies found that men’s number of sexual partners was positively related to their future SV behavior, with the exception of one study (Kingree & Thompson, 2013).…”
Section: Sexual Partners and Sv Perpetrationmentioning
confidence: 99%
“…Several studies have linked adolescents' and young adults' scripts for consensual sexual interactions to attitudes towards sexual coercion and to sexual aggression perpetration. In particular, the extent to which established behavioural risk factors for sexual aggression are part of the cognitive script for consensual sex was shown to predict the likelihood of engaging in sexually aggressive behaviour (D'Abreu & Krahé, 2014;Krahé, Bieneck, & Scheinberger-Olwig, 2007). One such behavioural risk factor is the use of alcohol in sexual interactions.…”
Section: Risky Sexual Scripts and Attitudes Towards Sexual Coercionmentioning
confidence: 99%